Video camera techniques - Millerson, Gerald (Media manuals., 1994)
Video Camera Techniques is an ideal starter guide for anyone owning a camcorder, newcomers to the field of broadcast or corporate video-making, or students who all wish to make videos to professional standards. Written in Gerald Millserson's easy to understand style, this step by step guide will help you to master the operation of your camera and quickly develop your own style and imaginative skills. This new edition now covers the latest types of video camera and gives guidance on camera handling and picture making form basics to advanced techniques. Gerald Millerson's books on video and television have long been acknowledged as among the best ever published. For more in-depth coverage of all aspects of video production his highly acclaimed Video Production Handbook is the definitive work on the subject. He is the author of two other titles in the Media Manuals series - Lighting for Video and Effective TV Production. His other books published by Focal Press are The Technique of TV Production (now in its 12th edition), The Techniques of Lighting for TV and Film and TV Scenic Design Handbook.